1990
DOI: 10.1007/bf02030251
|View full text |Cite
|
Sign up to set email alerts
|

Gonarthritis as only manifestation of chronic disseminated histoplasmosis

Abstract: A native from Surinam (South America), known to have a chronic gonarthritis for 20 years, died from an acute disseminated histoplasmosis. His gonarthritis was retrospectively shown to have been due to histoplasmosis. Although histoplasmosis rarely presents as a monarthritis, unacquaintance with this entity may result in fatal acute dissemination of the histoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Another 15-year review of 111 patients with systemic histoplasmosis revealed no cases with joint, bone, or tenosynovial involvement [2]. Other authors have described single case reports of bone [1, 10–12, 15, 22, 24] or joint [5, 7, 9, 13, 20, 23, 27, 30, 31] involvement throughout the extremities, including unusual cases of joint [20, 25] or bone [12, 15] involvement of the fingers or wrist, but all of these cases occurred in the absence of tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 15-year review of 111 patients with systemic histoplasmosis revealed no cases with joint, bone, or tenosynovial involvement [2]. Other authors have described single case reports of bone [1, 10–12, 15, 22, 24] or joint [5, 7, 9, 13, 20, 23, 27, 30, 31] involvement throughout the extremities, including unusual cases of joint [20, 25] or bone [12, 15] involvement of the fingers or wrist, but all of these cases occurred in the absence of tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common route of infection is pulmonary via inhalation of aerosolized spores, with lung involvement present in approximately 90 % of cases. Uncommonly other extrapulmonary sites of focal infection have been reported, including musculoskeletal manifestations of oligo- or monoarticular joint [5, 7, 9, 13, 20, 23, 27, 30, 31], bone [1, 10–12, 15, 22, 24], and rarely tenosynovial involvement [3, 4, 6, 8, 14, 1619, 21, 25, 26]. We report a case of histoplasmosis of the wrist and thumb flexor tendons presenting as an acute carpal tunnel syndrome (CTS) and tenosynovitis.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to articular histoplasmosis cases in humans in which the only presenting signs were painful and/or swollen joints. 12–16 Lameness has been reported as a less common clinical sign in other studies of histoplasmosis in cats, but it was not further characterized in those studies and there was no mention of synovial fluid findings. 2,4,6,7 Smaller joints (ie, tarsus, carpus) were most commonly affected in our study and this is consistent with previously reported findings in cats.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are RI = reference interval; TP = total protein; Alb = albumin; Glob = globulin; AST = aspartate aminotransferase; ALT = alanine aminotransferase; ALP = alkaline phosphatase; GGT = gamma-glutamyl transferase; T bili = total bilirubin; BUN = blood urea nitrogen; Creat = creatinine; P = phosphorus; Gluc = glucose; Ca = calcium; Mg = magnesium; Na = sodium; K = potassium; Cl = chloride; Chol = cholesterol; Trig = triglycerides; Amy = amylase; CPK = creatine phosphokinase similar to articular histoplasmosis cases in humans in which the only presenting signs were painful and/or swollen joints. [12][13][14][15][16] Lameness has been reported as a less common clinical sign in other studies of histoplasmosis in cats, but it was not further characterized in those studies and there was no mention of synovial fluid findings. 2,4,6,7 Smaller joints (ie, tarsus, carpus) were most commonly affected in our study and this is consistent with previously reported findings in cats.…”
Section: Discussionmentioning
confidence: 99%
“…Four case reports involved native knee joints [ 5–8 ] and 1 prosthetic hip joint [ 3 ]. Of these patients with knee involvement, 1 had leukemia [ 5 ], 1 had diabetes mellitus, polymyositis, and pulmonary interstitial disease [ 6 ], 1 had disseminated histoplasmosis [ 7 ], and 1 was on immunosuppression for polymyalgia rheumatica [ 8 ]. Our patient’s risk factors included diabetes mellitus, joint trauma (presence of joint prosthesis), and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%